Nonlinear response of doubly curved sandwich panels with CNT-reinforced composite core and elastically restrained edges subjected to external pressure in thermal environments - Tung, Hoang Van; Mai, Dao Nhu; Long, Vu Thanh (Vietnam Journal of Mechanics, 2021)
An analytical investigation on the nonlinear response of doubly curved panels constructed from homogeneous face sheets and carbon nanotube reinforced composite (CNTRC) core and subjected to external pressure in thermal environments is presented in this paper. Carbon nanotubes (CNTs) are reinforced into the core layer through uniform or functionally graded distributions. The properties of constituents are assumed to be temperature dependent and effective properties of CNTRC are determined using an extended rule of mixture. Governing equations are established within the framework of first order shear deformation theory taking into account geometrical imperfection, von Kármán–Donnell nonlinearity, panel-foundation interaction and elasticity of tangential edge restraints. These equations are solved using approximate analytical solutions and Galerkin method for simply supported panels. The results reveal that load carrying capacity of sandwich panels is stronger when boundary edges are more rigorously restrained and face sheets are thicker. Furthermore, elevated temperature has deteriorative and beneficial influences on the load bearing capability of sandwich panels with movable and restrained edges, respectively.